2018
DOI: 10.2174/1874220301805010119
|View full text |Cite
|
Sign up to set email alerts
|

T2 Versus T2* MRI Mapping in the Knee Articular Cartilage at 1.5 Tesla and 3 Tesla

Abstract: Background: Recently, several studies have shown that T2 and T2* MRI parametric mapping are sensitive to structural and biochemical changes in the extracellular cartilage matrix. The objective of this study was to assess, compare and correlate quantitative T2 and T2* relaxation time of the knee articular cartilage at 1.5 Tesla (T) and 3 Tesla. Methods: Thirty-eight symptomatic patients with knee articular cartilage di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The number of studies per population was described as total studies (number of studies reporting T 2 data & number of studies reporting T 2 * data): A total of 31 (22 T 2 & 13 T 2 * ) studies were included in the myocardial infarction (MI) population [26,, 11 (11 T 2 & 0 T 2 * ) in heart transplantation [27,[69][70][71][72][73][74][75][76][77][78] [188] ( Table 1). The absolute T 2 and T 2 * values are dependent on field strength [189,190], therefore the average mapping values were noted separately for 1.5 T and 3 T, and it was also used as covariate in the meta-regression analysis. T 2 and T 2 mapping obtained in control subjects were recorded as values from healthy subjects, unless the control population was explicitly defined otherwise in the "population" column of Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…The number of studies per population was described as total studies (number of studies reporting T 2 data & number of studies reporting T 2 * data): A total of 31 (22 T 2 & 13 T 2 * ) studies were included in the myocardial infarction (MI) population [26,, 11 (11 T 2 & 0 T 2 * ) in heart transplantation [27,[69][70][71][72][73][74][75][76][77][78] [188] ( Table 1). The absolute T 2 and T 2 * values are dependent on field strength [189,190], therefore the average mapping values were noted separately for 1.5 T and 3 T, and it was also used as covariate in the meta-regression analysis. T 2 and T 2 mapping obtained in control subjects were recorded as values from healthy subjects, unless the control population was explicitly defined otherwise in the "population" column of Table 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…T * 2 studies have shown good reproducibility. 6,14,15 T * 2 mapping offers unique information useful for the characterization of cartilage. T * 2 contrast captures shorter decay times in the cartilage and is less sensitive to bulk water.…”
Section: Summary Of Current Methods Used For Compositional Mri Of Car...mentioning
confidence: 99%
“…T2* mapping appears to be more sensitive in the detection of these changes than T2, with values that vary much later in the disease process. The variation in the relaxation times have, however, been found to be higher for T2 as compared to T2* in a study by Mars et al [ 21 ]. The results are better for MRI at higher strengths (3T) as compared to MRI at lower strengths (1.5T).…”
Section: Cartilage Imagingmentioning
confidence: 96%
“…While T2 mapping is SE-based, T2* is GRE-based and is thus more susceptible to magnetic field inhomogeneities. However, T2* uses shorter echo times (TE) and thus enables reduced scan times with higher resolution [ 18 , 19 , 20 , 21 ].…”
Section: Cartilage Imagingmentioning
confidence: 99%